2011
DOI: 10.1258/ebm.2011.010297
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunction of volume-sensitive chloride channels contributes to cisplatin resistance in human lung adenocarcinoma cells

Abstract: Cisplatin-based chemotherapy is the standard therapy used to treat non-small-cell lung cancer. However, its efficacy is largely limited due to the development of drug resistance. The exact mechanism in which cancer cells develop resistance to the drug is not yet fully understood. The purpose of the present study is to test the role of volume-sensitive Cl(-) channels in cisplatin resistance in human lung adenocarcinoma cells (A549 cells) using patch-clamp recording, cell volume measurement and apoptosis assay. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 37 publications
4
36
0
Order By: Relevance
“…In KCP-4 cells it was further shown that restoration of the channel's functional expression leads to a decrease in the cisplatin resistance (Lee et al, 2007). Similar results were obtained in human lung adenocarcinoma cells (Min et al, 2011). In wild type EATC, cisplatin treatment induced an AVD response, whereas MDR-EATC showed almost no AVD response when treated with cisplatin (Poulsen et al, 2010).…”
Section: Ion Transport and Drug Resistance In Cancersupporting
confidence: 87%
See 1 more Smart Citation
“…In KCP-4 cells it was further shown that restoration of the channel's functional expression leads to a decrease in the cisplatin resistance (Lee et al, 2007). Similar results were obtained in human lung adenocarcinoma cells (Min et al, 2011). In wild type EATC, cisplatin treatment induced an AVD response, whereas MDR-EATC showed almost no AVD response when treated with cisplatin (Poulsen et al, 2010).…”
Section: Ion Transport and Drug Resistance In Cancersupporting
confidence: 87%
“…Moreover, some studies have shown a decrease in Cl − permeability in various MDR cell models (Gollapudi et al, 1992; Lee et al, 2007; Poulsen et al, 2010; Min et al, 2011). The MDR-EATC and the KCP-4 human epidermoid cancer cells, which exhibit acquired resistance to cisplatin, both have strongly decreased VRAC activity (Lee et al, 2007; Poulsen et al, 2010).…”
Section: Ion Transport and Drug Resistance In Cancermentioning
confidence: 99%
“…78 In several multidrug-resistant cancer cell types, there is a reduction in VRAC, which limits the initial cell shrinkage, and hence protects the cell against apoptosis. 70,74,[80][81][82] Using multidrug-resistant EATC (MDR EATC) as an illustrative example, it is seen from . I/V relationships of the Cl -current in ELA cells in G0, G1, or (S) phase, following exposure to hypotonic extracellular solution and at nominally Ca 2C free concentration.…”
Section: Vrac In Apoptosis and In Multidrug Resistancementioning
confidence: 99%
“…However, several years ago the ethacrinic acid derivative DCPIB was found to selectively block swelling-activated Cl 2 currents (Decher et al, 2001). This compound is now increasingly used for probing the involvement of VRAC in physiologic and pathologic processes (see for example Best et al, 2004;Abdullaev et al, 2006;Harrigan et al, 2008;Rosenberg et al, 2010;Min et al, 2011;Sato et al, 2011).…”
Section: Introductionmentioning
confidence: 99%